Synthesis of (Polymer blend-MgO) Nanocomposites and Studying Electrical Properties for Piezoelectric Application - Majeed Habeeb; Rehab Shather Abdul Hamza (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2018)
Nanocomposites prepared by casting method with different percentages of nano magnesium oxide (0, 1.5, 3, 4.5 and 6) wt%.The structural and electrical properties of (PAA-CMC-MgO) nanocomposites were studied.The experimental results of Scanning electron microscopy shows the surface morphology of the (PAA-CMC-MgO)  nanocomposites where many aggregates or chunks randomly distributed on the top surface, homogeneous and coherent.The D.C electrical conductivity for (PAA-CMC-MgO) nanocomposites increased with increasing of temperature and magnesium oxid nanoparticles concentration, while activation energy decreases with increasing of the  magnesium oxid nanoparticles concentration.The A.C electrical properties show that the dielectric constant and dielectric loss of the nanocomposites decrease with increasing the frequency of applied electrical field and they increase with the increase of  the concentration of the magnesium oxide  nanoparticles. The A.C electrical conductivity increases with increasing the concentration of magnesium oxide nanoparticles and also increases with the increase frequency, as well as almost constant at high frequency.The results of sensor application showed that the electrical resistance of (PAA-CMC-MgO) nanocomposite decreases with increases in pressure.